Gender Affirmation as a Source of Resilience for Addressing Stigmatizing Healthcare Experiences of Transgender Youth of Color. Issue 12 (24th March 2021) - Goldenberg, Tamar; Gamarel, Kristi E; Reisner, Sari L; Jadwin-Cakmak, Laura; Harper, Gary W
Abstract: Background: Transgender and other gender diverse (TGD) youth of color experience stigma within healthcare. Gender affirmation can be a resilience resource; however, little is known about gender affirmation within healthcare. Purpose: This study explores TGD youth of color's experiences of stigma and gender affirmation across the entire healthcare experience and their role on motivation to seek care. Methods: In 2015, cross-sectional surveys and individual in-depth interviews were conducted among 187 TGD youth ages 16–24 living in 14 U.S. cities. Analyses followed a mixed-methods design whereby 33 participants were purposively selected for a qualitative phenomenological analysis based on quantitatively reported gender affirmation needs. Subsequent quantitative analyses examined how healthcare use differed by access to gender affirmation. Results: Participants qualitatively described experiencing stigma across multiple healthcare settings (e.g., primary care, emergency care, medical gender affirmation), including before (finding providers, scheduling), during (waiting rooms, provider interactions), and after (pharmacy) healthcare visits. Participants who quantitatively reported access to gender-affirming healthcare still described negative healthcare experiences, either because they accessed multiple healthcare services or because of prior negative experiences. Stigma and gender affirmation (both inside and outside of healthcare) influenced motivation to seek care, with variation depending on the type of care. Quantitative analyses confirmed these findings; access to gender affirmation differed for participants who delayed primary care vs. those who did not, but did not vary based on participants' use of medical gender affirmation. Conclusions: Findings highlight the importance of promoting gender-affirming healthcare environments to increase access to care for TGD youth of color. Abstract : Transgender and other gender diverse youth of color qualitatively describe the importance of having their gender affirmed within multiple types of healthcare settings.